Efektivitas Pembelajaran Tematik Terpadu dalam Implementasi Kurikulum 2013 Di MI. Miftahul Huda 01 Papungan Blitar - Haykal, Akhmad Fikri (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
This study aims to determine the effectiveness of integrated learning in the implementation of the2013 curriculum, the form of effectiveness that results from the planning process of learning,implementation of learning, assessment of learning and the use of teacher books and student books.This type of research is a qualitative descriptive study. The subject of this study was MI MiftahulHuda 01 Papungan Blitar Teacher. This study begins with knowing the field conditions andconducting observations. This study uses data collection techniques through observation andinterviews. Data analysis techniques consist of data reduction, data exposure, and conclusion. Theresults showed that the effectiveness of integrated thematic learning in the implementation of the 2013curriculum was indicated by the positive changes that occurred to the teacher in terms of making aLesson plan (RPP), by using it will be able to make more creative and life learning, carrying outassessments in accordance with the 2013 curriculum assessment standards, and using books otherrelevant supporters to supplement and develop material in the teacher's book and student books.Thus it can be concluded that integrated thematic learning is effective in implementing the 2013curriculum in MI. Miftahul Huda 01 Papungan Blitar.